Overview of Erythrocyte Index Values in Pregnant Women with Anemia at Kraton Regional General Hospital, Pekalongan Regency - Rohali, Amelia; Wibowo, Subur (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: The erythrocyte index is the average value or corpuscular value. The erythrocyte index value includes the average erythrocyte volume obtained from the MCV value. The average hemoglobin content in erythrocytes can be seen from the MCH, while the average hemoglobin concentration in erythrocytes is determined by the MCHC value. The erythrocyte index in pregnant women with anemia shows a decrease in MCV during the early stages of iron deficiency. The severity of anemia increases if the Mean Corpuscular Hemoglobin Concentration (MCHC) also decreases. This study aims to determine the profile of erythrocyte indices in pregnant women with anemia. Method: This study is a descriptive studyusing total sampling with 30 respondents. Result: The study obtained 17 erythrocyte index values with a percentage (56.67%) indicating hypochromic microcytic anemia, and 13 erythrocyte index values with a percentage of (43.33%) indicating normochromic normocytic anemia. Conclusion: The results of the study on erythrocyte index profiles in pregnant women with anemia at Kraton General Hospital, Pekalongan Regency, revealed 17 samples (56.67%) with hypochromic microcytic anemia, meaning the erythrocytes are small in size and pale in color. Additionally, 13 samples (43.33%) were found to have normochromic normocytic anemia, meaning they have normal size and color.